Differences between adolescents in secure residential care and non-residential educational facilities. (May 2022) - Pronk, Sanne; Germie, Van den Berg; Kuiper, Chris; Popma, Arne; Geert Jan, Stams; Mulder, Eva
Summary: In this cross-sectional study, we examined differences between 351 adolescents allocated to secure residential youth care and the non-residential alternative educational facility School2Care (12–18 years old, 63% boys). Data were collected by means of the official school registration system and standardized questionnaires. Findings: Results showed that adolescents in both settings had severe problems. Emergency situations, problems in daily functioning in all life domains, and previous out-of-home placements were found to be associated with allocation to secure residential youth care instead of non-residential alternative education. These three factors may be considered risk factors for secure residential placement of adolescents with complex needs. Applications: This study provides input for the prevention of secure residential youth care, because the two dynamic (changeable) risk factors for residential out-of-home placement (i.e., emergency situations and adolescent's daily life functioning) should be considered as intervention targets in non-residential care, while static factors (i.e., history of out-of-home placement) can be used to improve risk assessment of residential out-of-home placement, with higher risk requiring more intensive treatment according to the risk-need-responsivity model for effective mandated treatment.